STRATEGI KOMUNIKASI PEMASARAN MOBIL LOW COST GREEN CAR MELALUI SALES PROMOTION PADA PT. ASTRA INTERNASIONAL TBK CABANG CILEDUG KOTA TANGERANG - RINI LESTARI (Communication, 2015)
PT. Astra Internasional Tbk-Daihatsu-Ciledug is a single agency and official distributor of the Daihatsu in Indonesia. Marketing communications through sales promotion is one of the activities of PT.Astra Internasional Tbk-Daihatsu-Ciledug in promoting the product in the competition that is becoming more competitive.The purpose of this research is to find out and explain sales promotion as a strategy of marketing low cost car green car (lcgc) Daihatsu Ayla produced by PT. Astra Internasional Tbk Daihatsu  in Ciledug and constraints and opportunities in implementing the sales promotion.The theory used in this research is about marketing communication, that is, hotchpotch of marketing communications focused on sales promotion (kotler and keller). The research uses qualitative research approach , with research method of case study, method with in-depth interviews, observation and documentation..The result showed that the company: First, Astra Internasional Daihatsu Ciledug conduct sales promotion in the forms of: the refund cash discount, the frequency program, free gifts, free trials, product guarantee, the sales exhibition, and special advertising. Second, opportunities found in PT. Astra Internasional Daihatsu Ciledug in carrying out an activity to promote the sale of (sales promotion)include: facilitating the increase of the sales volume, facilitating the purchase of recurring repeat order, and facilitating the increase of customer loyalty .The constraints found in undertaking activities of sales promotion are as follows: the lack of human resources especially in the field of sales, PT .Astra Internasional Daihatsu Ciledug does not have the department  with specialty of handling marketing communications, and customers do not immediately make purchase decisions.